2008
DOI: 10.1111/j.1420-9101.2007.01491.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid evolution towards heavy metal resistance by mountain birch around two subarctic copper–nickel smelters

Abstract: Adaptations to pollution among long‐lived trees have rarely been documented, possibly because of their long reproductive cycles and the evolutionarily short timescales of anthropogenic pollution. Here, I present the results of a greenhouse experiment that suggest rapid evolutionary adaptation of mountain birch [Betula pubescens subsp. czerepanovii (Orlova) Hämet‐Ahti] to heavy metal (HM) stress around two copper–nickel smelters in NW Russia. The adaptation incurs a cost with reduced performance of adapted seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
37
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 76 publications
4
37
1
Order By: Relevance
“…It remains to be seen whether these results apply more generally or whether acid-stress tolerance is more costly in other plant species. Previous work on other types of tolerance indicates considerable variation among species in the cost of adaptation to stressful soil conditions (e.g., Hickey and McNeilly 1975;Macnair and Watkins 1983;Nicholls and McNeilly 1985;Harper et al 1997;Dechamps et al 2008;Eränen 2008).…”
Section: Genetic Constraintsmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains to be seen whether these results apply more generally or whether acid-stress tolerance is more costly in other plant species. Previous work on other types of tolerance indicates considerable variation among species in the cost of adaptation to stressful soil conditions (e.g., Hickey and McNeilly 1975;Macnair and Watkins 1983;Nicholls and McNeilly 1985;Harper et al 1997;Dechamps et al 2008;Eränen 2008).…”
Section: Genetic Constraintsmentioning
confidence: 99%
“…It is possible that nontolerant species lack the genetic variation necessary to increase their tolerance to lower soil pH (Macnair 1987;Al-Hiyaly et al 1990;Bradshaw 1991) or that genetic trade-offs between performance in favorable and stressful soil environments prevent populations from exploiting more acidic soils (Via and Lande 1985; see also Harper et al 1997;Dechamps et al 2008;Eränen 2008). However, there are still too few experimental studies to draw general conclusions about the relationship between a species' pH distribution in the field, the performance of the species under acidic conditions, and the pattern of genetic variation in pH or Al tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…As a timberline species it can survive in highly stressful study sites, and is known to have evolved ecotypes in relation to altitude (Weih and Karlsson 1999) and heavy metal pollution (Eränen 2008;Eränen et al unpublished). In previous studies in the highly stressful subarctic environments of the Kola Peninsula, NW Russia, we have shown that adult mountain birches facilitate conspecific seedlings and dwarf shrubs (Eränen andKozlov 2007, 2008;Zvereva and Kozlov 2004). However, earlier experiments did not address effects of mountain birch ecotypes (originated from high vs. low stress conditions) on intraspecific interactions in contrasting environments.…”
Section: Introductionmentioning
confidence: 96%
“…However, the traits advantageous in conditions of high stress are often deleterious under low stress, resulting in a trade-off of decreasing performance in non-local environments, thus facilitating the formation of locally adapted ecotypes (Futuyma 2001;Kawecki and Ebert 2004). Evolutionary adaptations can have significant effects on plant-plant interactions, of which the decreasing competitive ability of stress adapted genotypes is a common example (Eränen 2008;Kawecki and Ebert 2004;Linhart and Grant 1996). Recently, differences in stress tolerance (and related optima in growth conditions) among species have been shown to affect also positive interactions (facilitation), with species susceptible to stress usually benefiting most from neighbouring plants (Choler et al 2001;Liancourt et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…There also are numerous examples of plants developing resistance to polluted soils (e.g. Eranen 2008). Thus, long-term exposure to environmental stressors can result in physiological responses, or alterations in the genetic makeup of a population brought about by selection for favourable traits.…”
Section: Introductionmentioning
confidence: 99%